Synthesis and biological evaluation of a monocyclic Fc-binding antibody-recruiting molecule for cancer immunotherapy. Issue 3 (21st January 2021) - Sasaki, Koichi; Muguruma, Kyohei; Osawa, Rento; Fukuda, Akane; Taniguchi, Atsuhiko; Kishimura, Akihiro; Hayashi, Yoshio; Mori, Takeshi; Katayama, Yoshiki
Abstract : A monocyclic Fc-binding peptide "15-Lys8Leu" enables simple preparation of a Fc-binding antibody-recruiting molecule (Fc-ARM), which induces potent cytotoxicity against folate receptor positive cancer cells via NK cell-mediated immune response. Abstract : Antibody-recruiting molecules (ARMs) are bispecific molecules composed of an antibody-binding motif and a target-binding motif that redirect endogenous antibodies to target cells to elicit immune responses. To enhance the translational potential of ARMs, it is crucial to design antibody/target-binding motifs that have strong affinity and are easy to synthesize. Here, we synthesized a novel Fc-binding ARM (Fc-ARM) that targets folate receptor (FR)-positive cancer cells, Reo-3, using a recently developed monocyclic peptide 15-Lys8Leu, which binds strongly to the Fc region of an antibody. Reo-3 bound to the Fc region of the antibody with a K d of 5.8 nM, and recruited a clinically used antibody mixture to attack FR-positive IGROV-1 cells as efficiently as Fc-ARM2, in which a bicyclic Fc-binding peptide was used. These results indicate that 15-Lys8Leu, which can be synthesized readily, is suitable for various applications including the development of Fc-ARMs.